Role of Media in HIV/AIDS Awareness - Dr. Vinod Kumar (Journal of Linguistics and Communication Studies, 2024)
Mass media, particularly, newspapers, magazines, journals, leaflets, television and radio have helped to provide information and create awareness among the people about HIV and other health related issues. In a country with a large illiterate population, many people tend to think that sicknesses like HIV-AIDS, other sicknesses and physical or mental disabilities are a result of punishment of God, fate or one’s Karma. As a result, many choose superstitious practices like witchcraft, magic, sacrifices etc. instead of adopting scientific and medical methods. If we want to provide information and education on important health related issues, we need to mount and sustain a major public education campaign. Media can play a key role in creating awareness about AIDS, spreading knowledge about its symptoms, the mode of transmission, methods of preventing infection etc. Media also help to keep us abreast with latest information and data gathered from various studies and researches going on in the field. In this research paper highlights the kinds, methods, types and role of Media in HIV/AIDS Awareness.